MENGHIDUPKAN PEMBELAJARAN AL-QURAN HADIST MELALUI METODE EFEKTIF GALLERY WALK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XII DI MA UNGGULAN NUR AL-JADID WARU - Firda Nuriyah; Istifaiyyatul Qudsi; Ilham Abimanyu; Rizky Agustina Aulia; M. Sholehuddin Sulaiman (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This study aims to determine teacher activity and the extent to which student learning outcomes can increase with the application of the gallery walk model in learning Al-Qur'an Hadith for class XII MA Unggulan Nur Al-Jadid, Waru sub-district, Sidoarjo Regency for the 2024/2025 academic year. This research was prepared using the method of classroom action research (PTK), which was designed within a period of two cycles and each cycle each has four stages including a) planning (planning), b) action (acting), c) observation (observing), and d) reflection (reflecting). The research subjects were taken from class XII students of MA Unggulan Nur Al-Jadid Waru District, totaling 20 students, in the 2024/2025 school year. Instruments Teacher activity observation results and learning outcomes test questions as data used to find the shortcomings and advantages of direct work practice activities. Based on the observation data of cycle I, the overall value of the teacher activity sheet observation results from 20 students is 71.73% which is classified as good. According to the data from the second cycle observation, the teacher activity sheet showed an increase in results of 92.39% which is classified as quite high or very good. While student learning outcomes in cycle I were 14 students with a complete description who had a classical completeness presentation value of 70%, but had an unfinished category. Continued in cycle II, where 19 students with a percentage of classical completeness of 95% had a complete category. The increase in teacher activity and student learning outcomes during the learning process with the use of the gallery walk learning approach by causing student learning achievement to increase, thus the improvements made over 2 cycles are considered to have achieved the expected success indicators.